Kabitta Bhāī Guradāsa : dūsarā skandha : bhāwa prakāshaṇī ṭīkā sameta - Guradāsa, Bhai, ca. 1555-1629, a. 1555-1629 (SAMP early 20th-century Indian books project ;, 1950)
Critical edition of Kabitta sawaiye, verse work on Sikhism.